Optimization of Anti-SARS-CoV-2 Neutralizing Antibody Therapies: Roadmap to Improve Clinical Effectiveness and Implementation - van der Straten, Karlijn; van Gils, Marit J.; de Taeye, Steven W.; de Bree, Godelieve J. (Frontiers in Medical Technology, 2022)
One of the major breakthroughs to combat the current Coronavirus Disease 2019 (COVID-19) pandemic has been the development of highly effective vaccines against the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Still, alternatives are needed for individuals who are at high risk of developing severe COVID-19 and are not protected by vaccination. Monoclonal antibodies against the spike protein of SARS-CoV-2 have been shown to be effective as prophylaxis and treatment against COVID-19. However, the emergence of variants of concern (VOCs) challenges the efficacy of antibody therapies. This review describes the neutralization resistance of the clinically-approved monoclonal antibody therapies against the Alpha (B.1.1.7), Beta (B.1.351), Gamma (P1), Delta (B.1.617.2), and the Omicron (B.1.1.529) variants. To guide the development of monoclonal antibody therapies and to anticipate on the continuous evolution of SARS-CoV-2, we highlight different strategies to broaden the antibody activity by targeting more conserved epitopes and/or simultaneously targeting multiple sites of vulnerability of the virus. This review further describes the contribution of antibody Fc effector functions to optimize the antibody efficacy. In addition, the main route of SARS-CoV-2 antibody administration is currently intravenously and dictates a monthly injection when used as prophylactic. Therefore, we discusses the concept of long-acting antibodies (LAABs) and non-intravenously routes of antibody administration in order to broaden the clinical applicability of antibody therapies.